Analysis of Mercury Heavy Metal Content in Climbing perch fish (Anabas testudineus) from Rawa Taliwang Lake - Khairuddin, Khairuddin; Yamin, M.; Kusmiyati, Kusmiyati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
The heavy metal mercury is at risk of disrupting brain development in children if it accumulates in the human body. The aim of the study was to determine the content of heavy metal mercury (Hg) in Climbing perch fish (Anabas testudineus) originating from Rawa Taliwang Lake to enrich the Ecotoxicology course material. The special benefit is to protect consumers who consume fish from heavy metal contaminants. The research was conducted in Rawa Taliwang Lake, which is in an area submerged in water. There are 2 research stations, namely in the eastern and western parts of the lake. Gill nets were used to catch fish. Fish samples were taken 3 to 4 times at each station. The Fish species taken was the Climbing perch fish (A. testudineus). Furthermore, each fish sample was put into a plastic bag and then stored in a sample box. The research sample was then analyzed at the Environmental Laboratory Center for the West Nusa Tenggara Environment and Forestry Office. The method of data analysis was carried out by taking muscle tissue from fish and then analyzing the content of heavy metals in the form of Hg using an Atomic Absorption Spectrophotometer (AAS). The wet destruction stage in the destruction sample is the process of degradation of organic material samples by utilizing strong acidic liquids, namely HNO3, as a destructive agent. The data obtained are in the form of Pb heavy metal levels in ppm (parts per million). The next stage is that the Pb concentration obtained is processed descriptively and then displayed in table form according to the AAS results. The conclusion of this study is that the heavy metal content of Hg in Climbing perch fish (A. testudineus) originating from Rawa Taliwang Lake to enrich Ecotoxicology course material was <0,0001 ppm.